Recopilación de la memoria historica del "Parque del Chontaduro" como patrimonio y espacio representativo de la ciudad de Cali (2018)
This work focuses on the recovery of the stories that recreate the development of the collective memory of the Cali people, through the historical reconstruction of the Vallecilla family, who made part of the first years of the park, investigating in its main social actor the Mr. Omar Vallecilla, who as part of the group of founders of the park, continues generating around the chontaduro, not only a life story, but also the economic maintenance of their families, which become a legacy that is shared with visitors and inhabitants of the community of Parque del Chontaduro.